Data hiding for fighting piracy. - Barni, M.
The problem of digital content piracy is becoming more and more critical, and major content producers are risking seeing their business being drastically reduced because of the ease by which digital contents can be copied and distributed. This is the reason why digital rights management (DRM) is currently garnering much attention from industry and research. Among the various technologies that can contribute to set up a reliable DRM system, data hiding (watermarking) has found an important place due to its potentiality of persistent attaching some additional information to the content itself. In this article, we analyzed the possible use of data hiding technology in DRM systems. The article also gives a brief survey of the main characteristics of the most common data hiding methods such as proof of ownership, watermark, copyright protection, infringement tracking, copy control, and item identification. The article also investigates the different approaches by highlighting critical points of each approach in particular from the point of view of hostile attacks.
Keywords: Copy control; Copyright protection; Data hiding technology; Digital content piracy; Digital rights management; Infringement tracking; Item identification; Proof of ownership; Watermarking